Praktik Pembukaan Lahan dengan Teknik Membakar oleh Masyarakat di Limboro Rambu-Rambu Kabupaten Majene - K, Qaizar (Program Studi Kehutanan Fakultas Pertanian dan Kehutanan Universitas Sulawesi Barat, 2022)
This study aims to identify the practice of land clearing with burning techniques by the community in Limboro Rambu-Rambu Village, Majene Regency. The research was conducted from September 2020 to June 2021. Data collection used an accidental non-probability sampling technique with 30 respondents. Data analysis was carried out using a descriptive analysis method.The results of the study showed that in Limboro Rambu-Rambu Village there were two methods of land clearing that were commonly carried out by the community, namely the burning technique or “metunu” which was a technique of burning with heaps. The second technique is the non-deposit combustion technique using fuel. The stages of the combustion process consist of 2 (two), namely the first combustion stage and the second combustion stage which is called “mokafo”.